The effect of Islamic values in reducing organizational conflict A field study in some of the institutions operating in Al-Jouf region in the Kingdom of Saudi Arabia - Abdelrahim Shazali yahia Abduallh; Abdelnaser Abdulallah mohamed Aissa (Dirassat Journal Economic Issue, 2016)
This study aims to identify the Islamic religious values that help in reducing organizational conflict, as well as to define the concept of organizational conflict. The subject matter of the research can be summarized in How to apply Islamic values in private sector organizations in Al-Jouf region, north of Saudi Arabia to reduce conflicts in such these organizations?. The researcher used descriptive statistics, means, standard deviations, percentages and (t. test) to analyze the study results. The main results of this study that the application of Islamic values ​​by workers helps to reduce regulatory conflicts in the work environment. And that the absence of the application of Islamic religious values ​​will lead to the occurrence of organizational conflict in the business organizations environment